CARACTERIZAÇÃO GENÉTICA E DISTRIBUIÇÃO GEOGRÁFICA DO VÍRUS RÁBICO ISOLADO DE BOVINOS NO ESTADO DE MATO GROSSO, BRASIL - Matta, G.c.a.; Nociti, D.l.p.; Carvalho, A.a.b [UNESP]; Samara, S.i. [UNESP]; Ito, F.h; Sakai, T; Itou, T; Sato, G; Kobayashi, Y; Mochizuki, N (Instituto Biológico, 2020)
A total of 53 rabies virus (RV) isolates originating from cattle in the state of Mato Grosso, Brazil, were genetically characterized. Partial nucleoprotein gene sequences of these isolates were phylogenetically and geographically analyzed. Cattle isolates, which clustered with the vampire bat related RV group, were further subdivided into 7 subgroups. These subgroups were distributed widely in lowland regions, with some subgroups separated from each other by small mountains and hydrographical features. These results indicate that cattle rabies is derived from several regionally-defined variants, which suggests that its geographical distribution is related to that of the vampire bat population.

Foram caracterizados, geneticamente e geograficamente, o sequenciamento parcial da nucleoproteína (gene N) de 53 isolados do vírus da raiva (VR) originários do Estado de Mato Grosso, Brasil. Os isolados de bovinos, que se encontravam no grupo do VR relacionado a morcegos hematófagos, foram posteriormente subdivididos em sete subgrupos genéticos. Estes subgrupos foram distribuídos em regiões de terras planas, com alguns subgrupos separados por formações de pequenas montanhas e hidrografia. Estes resultados indicam que a raiva em bovinos é derivada de diversas variantes regionalmente definidas, o que sugere que sua distribuição geográfica está relacionada as populações de morcegos hematófagos.
GENETIC CHARACTERIZATION AND GEOGRAPHIC DISTRIBUTION OF RABIES VIRUS ISOLATES FROM CATTLE IN MATO GROSSO, BRAZIL
Keywords: Rabies virus; cattle; RT-PCR; phylogenetic analysis; geographical analysis; Vírus da raiva; bovinos; análise filogenética; análise geográfica